2021
DOI: 10.1111/jre.12910
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs: Emerging roles in periodontitis

Abstract: Periodontitis is a major burden of public health, affecting 20%–50% of the global population. It is a complex inflammatory disease characterized by the destruction of supporting structures of the teeth, leading to tooth loss and the emergence or worsening of systematic diseases. Understanding the molecular mechanisms underlying the physiopathology of periodontitis is beneficial for targeted therapeutics. Long non‐coding RNAs (lncRNAs), transcripts made up of more than 200 nucleotides, have emerged as novel reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 119 publications
1
7
0
Order By: Relevance
“…In recent years, long non-coding RNA (lncRNA) has been proven that participated in the progression of periodontitis [ 15 ]. LncRNAs are a class of transcripts longer than 200 nucleotides that do not encode protein.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, long non-coding RNA (lncRNA) has been proven that participated in the progression of periodontitis [ 15 ]. LncRNAs are a class of transcripts longer than 200 nucleotides that do not encode protein.…”
Section: Introductionmentioning
confidence: 99%
“…Most lncRNAs have been studied in relation to processes such as carcinogenesis, osteogenesis, diabetes, neurological diseases, and cardiovascular diseases [ 98 ], suggesting their important role as regulators in the interaction between pathogens and hosts. Emerging evidence has suggested that long non-coding RNAs (lncRNAs) are linked to alterations in immune-related genes and cell subpopulations, including regulating T cells through FOXP3 [ 99 ], controlling dendritic cell differentiation through STAT3 binding to lncDC [ 100 ], and activating the differentiation of CD4+ and CD8+ T cells [ 101 ]. Their involvement in immune response make them valuable diagnostic, prognostic, and therapeutic targets for several inflammatory diseases.…”
Section: Epigenetic Regulations In the Pathophysiology Of Periodontal...mentioning
confidence: 99%
“…The first is according to the diagnostic information requested, such as predictive, initial diagnostic, prognostic and maintenance biomarkers [ 92 ]. The second one is in the function of the biological type, where it is currently known that there are different types of inflammatory mediators, tissue degradation products, bone resorption markers, microbial agents, proteolytic enzymes [ 91 , 93 ], non-coding RNAs [ 93 , 94 , 95 , 96 ] and single nucleotide polymorphisms (SNPs) [ 97 ] ( Figure 2 ).…”
Section: Oral Biomarkersmentioning
confidence: 99%